2017
DOI: 10.1002/cphc.201600442
|View full text |Cite
|
Sign up to set email alerts
|

Towards Understanding the Solvent‐Dynamic Control of the Transport and Heterogeneous Electron‐Transfer Processes in Ionic Liquids

Abstract: The impact of temperature-induced changes in solvent dynamics on the diffusion coefficient and standard rate constant k for heterogeneous electron transfer (ET) of ethylferrocene (EFc) in 1-butyl-3-methylimidazolium hexafluorophosphate ([BMIM][PF ]) is investigated. The results are analysed to understand the impact of solvent-dynamic control, solute-solvent interactions and solvent friction on the transport of redox probes and k . Concentration dependence of the diffusion coefficient of EFc in [BMIM][PF ] is o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 139 publications
(355 reference statements)
0
5
0
Order By: Relevance
“…With no dielectric solvent, the constituent ions do not exist as simple spherical charges. 6 Rather, the ions exist as ion pairs. From a fundamental electrochemical perspective, the use of RTILs allows one to investigate electron-transfer kinetics and redox reaction mechanisms of soluble redox systems in the absence of a dielectric solvent.…”
Section: ■ Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…With no dielectric solvent, the constituent ions do not exist as simple spherical charges. 6 Rather, the ions exist as ion pairs. From a fundamental electrochemical perspective, the use of RTILs allows one to investigate electron-transfer kinetics and redox reaction mechanisms of soluble redox systems in the absence of a dielectric solvent.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The short-and long-range organizations of the RTIL ions at an electrified interface, as well as their unique arrangement around a redox molecule, make the electrochemical properties of these novel media interesting to study. 6 The chemical and electrochemical stability of RTILs leads to a large voltammetric working potential window of 4−6 V, depending on the RTIL cation and anion. Electrochemical reactions in RTILs will be influenced by the arrangement of the ions at the electrified interface between the RTIL and the solid surface, and the RTIL's physicochemical properties (e.g., electrical conductivity and viscosity).…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…17 Estimation of the heterogeneous electron-transfer rate constants for the ferrocene-ferrocenium system has been studied by Fawcett et al 18 and others. 19,20 Bard et al 21 reported that [Ru(bpy) 3 ] 2+/3+ has k s = 0.24 cm s −1 in DMF using a Pt electrode, yet Scott et al 6 found k s = 9.5 ± 3.9 cm s −1 (298 K) in DMF using a Pt electrode with 0.75 M LiCF 3 SO 3 as supporting electrolyte. Unfortunately, there is no temperature dependence given for both results.…”
mentioning
confidence: 99%